The Relationship Between The Physical Environment and Quality of Life for Patients With Type 2 Diabetes Mellitus - Haerani,; Amiruddin, Ridwan; Ansariadi,; Arsin, A. Arsunan; Suriah,; Seweng, Arifin; Zaenab, (International Journal of Statistics in Medical Research, 2023)
Background: Diabetes Mellitus (DM) is a chronic disease with a high mortality rate and can affect a person's quality of life. One of the factors determining the quality of life is the physical environment, such as temperature, humidity, lighting, noise, and PM2,5. Objective: To determine the relationship between the physical environment and the quality of life of type 2 DM patients at the Barombong Community Health Center, Makassar City. Materials and Methods: This research uses a study design case-control with purposive sampling. Interviews were conducted with the WHOQol questionnaire and measuring the physical environment in 138 patients with type 2 diabetes then analyzed with the odd ratio test and logistic regression on the Stata application. Results: The results obtained showed a non-significant relationship for the variables humidity, lighting and PM2,5 on the quality of life of type 2 DM patients due to value-p > 0.05 while the variables related to the quality of life of type 2 DM patients are house temperature (OR=4.833; 95% CI: 2.121-11.481) and noise (OR=4.723; 95% CI: 2.075-10.895) with a probability of type 2 DM with unqualified temperature and noise having a poor quality of life of 73.9%. Conclusion: The most significant factor that affects the quality of life of people with type 2 diabetes mellitus is their home temperature.